2012
DOI: 10.2166/wst.2012.382
|View full text |Cite
|
Sign up to set email alerts
|

Volatilization of hydrogen sulfide from a quiescent surface

Abstract: Air-water mass transfer of hydrogen sulfide from a shallow tank with a quiescent surface under the influence of weak wind stress on the water surface was studied numerically using a two-dimensional model. The flow field in the tank was investigated using a computational code based on a finite volume, which is used to numerically solve momentum, mass and continuity conservation equations. The results show that water phase flow field is strongly dependent on the wind-induced surface velocity and the aspect ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Resistance to transport through a crust is related to the porosity of the crust (de Cassia Feroni et al., 2012). There was no trend in r s over the summer until the 2 days of measurement after August 10.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to transport through a crust is related to the porosity of the crust (de Cassia Feroni et al., 2012). There was no trend in r s over the summer until the 2 days of measurement after August 10.…”
Section: Resultsmentioning
confidence: 99%
“…Transport of H 2 S through the slurry liquid is due to molecular diffusion (Arogo, et al., 1999; Olesen & Sommer, 1993, convection through shearing action at the liquid/air interface (de Cassia Feroni et al., 2012), convection of bubbles formed when H 2 S production exceeds liquid molecular diffusion (Ni et al., 2009), and buoyant convection (MacIntyre et al., 2002). Shearing by the wind moving over the slurry surface decreases the resistance to atmospheric transport (Arogo et al., 1999), increases the mixing within the slurry, and possibly bursts bubbles at the surface of the manure.…”
Section: Introductionmentioning
confidence: 99%
“…Except by Andreão et al (2019), authors have been using a constant contaminant flow rate or a constant concentration value as a boundary condition at the liquid-gas interface for mass transfer investigations, as an alternative to monophasic system simulations. Since these surface-imposed boundary conditions are not realistic, as the volatilization of chemical compounds such as H 2 S depends on the flow velocity at the liquid-gas interface (Feroni et al, 2012), the alternative for monophasic system simulations is to use algebraic models. Andreão et al (2019) showed the potential use of algebraic models as a boundary condition at the liquid-gas interface.…”
Section: Introductionmentioning
confidence: 99%